Response to Comments on: "Nonlinear phenomena, bifurcations, and routes to chaos in an asymmetrically supported rotor-stator contact system" by Philip Varney, Itzhak Green [J. Sound Vib. 336 (2015) 207-226]. (24th November 2017) - Varney, Philip; Green, Itzhak
Abstract: The authors would like to thank the discussers for their interest in the paper. The discussers raise several objections to the original work; namely, that the state-space equations of motion were derived incorrectly, thus rendering the original results incorrect by association. In actuality, the error in the original state-space equations (Eq. (16) in the original work) is typographic only. This, in conjunction with a typographic error in Table A1, prevented the discussers from replicating a subset of the original results (though the discussers were able to replicate many of the results presented in the original work, despite the presumed error in the equations). These typographic errors are rectified here. In addition, results are presented here corresponding to the solution that would have been obtained had the state-space equations been incorrect in the manner presumed by the discussers. Finally, the discussers state that the results presented in the original work do not adhere to physical principles because the steady-state solution in one case indicates contact even though the linear response to imbalance is less than the radial clearance. This seeming discrepancy is also addressed here.